Synthesis and characterization of a new TiZrHfNbTaSn high-entropy alloy exhibiting superelastic behavior. (June 2021) - Gao, J.J.; Castany, P.; Gloriant, T.
Abstract: In this study, a new single-phase bcc Ti35 Zr35 Hf15 Nb5 Ta5 Sn5 high-entropy alloy (HEA) was developed and investigated by means of cyclic tensile tests, transmission electron microscopy (TEM), electron back-scattered diffraction (EBSD) and in situ synchrotron X-ray diffraction (SXRD). The alloy reveals a superelastic behavior due to the reversible stress-induced martensitic transformation that occurs between the β phase and the α'' phase. A high strain recovery of 3.8% is obtained by tensile test, which is attributed to the <110>β {447}β recrystallization texture observed. Graphical abstract: Image, graphical abstract